2020
DOI: 10.1097/dss.0000000000002323
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Complications and Recurrences After Surgical Interventions in Hidradenitis Suppurativa

Abstract: BACKGROUND The possible connection between hidradenitis suppurativa (HS) patients undergoing surgery and higher complications/recurrences has been implied, but inconsistent results reported. OBJECTIVE To assess the complication and recurrence rates for HS patients undergoing surgery and to evaluate whether known HS comorbidities and habits (smoking, obesity and diabetes) have an effect on the complication and recurrence rates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 75 publications
5
29
0
Order By: Relevance
“…A study by Ovadja et al 2 in The Netherlands, of 107 surgical interventions for HS for 54 patients, found a 32% recurrence rate after a median 30month follow-up period. The 8 week healing time of the current study is also comparable to the 6 weeks that Ovadja et al 2 reported and the 3.3 months reported by Fertitta et al 1 A systematic review by Bouazzi et al 3 found that, of 54 relevant articles on post-operative HS complications and recurrences, there was an overall mean complication rate of 24% and a mean recurrence rate of 20%. Due to the high rates of post-surgical recurrence for HS in the literature, a retrospective review of surgical treatment of HS 4 concluded that recurrence of HS should be viewed as a feature of the Figure 2 Recurrence rates following first, second and third surgery.…”
Section: Hidradenitis Suppurativa: a Review Of Post-operative Outcomessupporting
confidence: 86%
See 1 more Smart Citation
“…A study by Ovadja et al 2 in The Netherlands, of 107 surgical interventions for HS for 54 patients, found a 32% recurrence rate after a median 30month follow-up period. The 8 week healing time of the current study is also comparable to the 6 weeks that Ovadja et al 2 reported and the 3.3 months reported by Fertitta et al 1 A systematic review by Bouazzi et al 3 found that, of 54 relevant articles on post-operative HS complications and recurrences, there was an overall mean complication rate of 24% and a mean recurrence rate of 20%. Due to the high rates of post-surgical recurrence for HS in the literature, a retrospective review of surgical treatment of HS 4 concluded that recurrence of HS should be viewed as a feature of the Figure 2 Recurrence rates following first, second and third surgery.…”
Section: Hidradenitis Suppurativa: a Review Of Post-operative Outcomessupporting
confidence: 86%
“… 1 A systematic review by Bouazzi et al. 3 found that, of 54 relevant articles on post-operative HS complications and recurrences, there was an overall mean complication rate of 24% and a mean recurrence rate of 20%. Due to the high rates of post-surgical recurrence for HS in the literature, a retrospective review of surgical treatment of HS 4 concluded that recurrence of HS should be viewed as a feature of the disease that can be anticipated and managed rather than a failure of surgical treatment.…”
mentioning
confidence: 99%
“…Flap reconstructions of HS have been widely reported, but often suffer complications. 5,8,9 Flap dehiscence and associated complications may be explained by the chronicity of the underlying tissues, poor vascularity, and potential for dead space between the flap and the underlying fascial layer. It was hypothesised that placement of an ECM bioscaffold as an implant under the fasciocutaneous flap may reduce these complications as the graft would be infiltrated and remodelled to provide a deeper layer of well-vascularised new tissue.…”
Section: Discussionmentioning
confidence: 99%
“…7 Recurrence rates after a wide excision appear lower than after local excision; 5 however, the extent of tissue removal means that healing time is longer and complications more likely. Bouazzi et al 8 found that complication rates and recurrence rates remain relatively high at 25.1% and 14.0%, respectively. Ovadja et al 9 estimated recurrence rates for wide and partial excisions at 5% and 26%, respectively, from a meta-analysis of 125 articles.…”
mentioning
confidence: 99%
“…Radical surgery remains a cornerstone in the management of severe HS/AI achieving complete remissions with aggressive treatment. [15][16][17][18][19][20][21][22][23][24] In a single center trial, 81% of surgically treated patients considered the surgery the best treatment for their disease. 21 A meta-analysis of surgery in HS/AI of 54 trials indicated an overall mean complication rate of 24% and a mean recurrence rate of 20.1%.…”
Section: Current Treatmentmentioning
confidence: 99%